Opportunity in uncertainty: small business response to COVID-19 - Megan Chapman Cook; Steven J. Karau (Innovation & Management Review, 2023)
Purpose - The global spread of coronavirus brought the economy to a screeching halt as entrepreneurs faced constraints in their ability to transact business. Mandatory shutdowns of businesses, travel restrictions and other measures were taken. This study aimed to explore adaptations of small businesses for surviving in such a turbulent environment. Design/methodology/approach - The authors conducted exploratory research with detailed interviews with 15 small business owners from various industries in rural communities in the Midwestern United States. Findings - The study revealed a variety of strategic responses and highlighted creativity and flexibility in coping with uncertainty. Business owners adapted their strategies regarding processes, products and target customers to remain flexible and reallocate resources to meet ever-changing demands. Some created and strengthened relationships with other business owners, clients, customers and the community. Several showed optimism for the long-term, whereas others viewed survival as contingent on a speedy return to normalcy. Research limitations/implications - A modest sample of fifteen small business owners were interviewed in similar communities in the Midwest using snowball sampling. With a larger sample size and more variance in age and gender, interview responses may be more diverse and potentially more generalizable. However, the current research may provide some unique insights for younger, up-and-coming entrepreneurs in smaller cities and communities regarding some effective small business and community response to uncertainty and change. Originality/value - The coronavirus pandemic provided a unique environment to gain insight into entrepreneurial adaptation to unpredictable crisis situations and highlights the importance of assessing and adjusting business strategies to constantly changing demands. The authors also present an emergent theoretical process model of small business adaptive responses to uncertainty that summarizes the major themes derived from the interview responses.
Keywords: 650; Adaptation; Change; Crisis; Entrepreneurship; Flexibility; Innovation; Strategy; Uncertainty